2021
DOI: 10.1515/amylase-2021-0001
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus infantarius 25124 isolated from pozol produces a high molecular weight amylopullulanase, a key enzyme for niche colonization

Abstract: Pozol is a beverage made with maize dough that is prepared after boiling the kernels in limewater, causing a decrease in soluble sugars, with starch being the main fermentable carbohydrate in the dough. Previously, Streptococcus infantarius ssp. infantarius 25124 (Sii-25124) was identified as the most amylolytic bacteria isolated in this product. Analysis of Sii-25124 amylolytic enzymes revealed two amylases, a cytoplasmic α-amylase of 55.7 kDa and an extracellular amylopullulanase of 246.3 kDa, with two catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…The differential behavior of the activities of α-amylase and pullulanase regarding certain metal ions (such as Ca 2+ , Hg 2+ , and Mg 2+ ) may be due to the presence of two different active sites, one for the α-amylase and the other for the pullulanase [63]. Compared to the control, the effect of divalent ions on amylolytic activity showed that the presence of Mg 2+ increased amylolytic activity by 146%, while Mn 2+ , Fe 3+ , Ca 2+ , and Na + increased amylolytic activity to 141%, 116%, 112%, and 111%, respectively [41]. It is known that most amylases are considered metalloenzymes, which are enzymes that require metal ions (usually Ca 2+ ) to maintain their stable native structure.…”
Section: Salts Alpha Amylasementioning
confidence: 98%
See 1 more Smart Citation
“…The differential behavior of the activities of α-amylase and pullulanase regarding certain metal ions (such as Ca 2+ , Hg 2+ , and Mg 2+ ) may be due to the presence of two different active sites, one for the α-amylase and the other for the pullulanase [63]. Compared to the control, the effect of divalent ions on amylolytic activity showed that the presence of Mg 2+ increased amylolytic activity by 146%, while Mn 2+ , Fe 3+ , Ca 2+ , and Na + increased amylolytic activity to 141%, 116%, 112%, and 111%, respectively [41]. It is known that most amylases are considered metalloenzymes, which are enzymes that require metal ions (usually Ca 2+ ) to maintain their stable native structure.…”
Section: Salts Alpha Amylasementioning
confidence: 98%
“…A previous work [41] reported the optimal temperature and pH of amylopullulanase from Streptococcus infantarius ssp. as 37 • C and 6.8, respectively.…”
Section: Thin Layer Chromatography (Tlc)mentioning
confidence: 99%
“…Consequently, the core microbiota responsible for corn fermentation is expected to have this metabolic capacity, as has already been shown in S. infantarius , isolated from pozol [14, 43]. On the other hand, while the alkaline thermal treatment associated with nixtamal removes most soluble sugars, it also predigests complex insoluble carbohydrates from the plant cell wall, increasing the availability of arabinoxylan, the main component of the hemicellulose present in fermented maize dough [44, 45].…”
Section: Resultsmentioning
confidence: 95%
“…Characterization of the most amylolytic LAB species, Streptococcus infantarius subsp. infantarius , produced two amylases, an amylopululanase with debranching capacity and an α-amylase ( 9 , 57 ).…”
Section: Discussionmentioning
confidence: 99%